Celebrities enhance food tourism: A chef in the city or a city by the chef? (Research Note) - Francesc Fusté-Forné (Dos Algarves, 2023)
During the past decades, studies have paid growing attention to the relationships between celebrities and tourism because of their influence on travel behaviours. Based on the literature on celebrity-induced film tourism, chefs have emerged as a source of celebrity-induced food tourism, which awards value to food as art. This exploratory research note is focused on the culinary empire of Karlos Arguiñano in Zarautz (Basque Country, Spain) and argues that celebrity chefs are powerful cultural and social agents who have developed their own brands and influence on food consumption. This research innovatively illustrates the potential of celebrity chefs for food tourism management and marketing.